How anthropological approach address social determinants of health in Asmat, Papua - Jodi Visnu (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
Indonesia faced one of the most tragic and challenging health problems at the beginning of 2018, many children in Papua's Asmat Regency were suffering from malnutrition and measles. More than a thousand children were treated while 78 children under five years of age have died, mostly indigenous children. Asmat Regency is located in Indonesia's easternmost province with poor infrastructure and communication networks, also high transportation costs due to swampy regions criss-crossed by rivers, hard-to-reach from the center to the districts. Asmat's belief in their ancestors has formed their way of life and shaped their behavior, choices, and attitudes towards health issues, such as poor awareness regarding the fulfillment of daily nutritional intake, which is potentially harmful. Curative care is the highest priority in an extraordinary incident such as an outbreak or a mass-casualty disaster. However, establishment of the cultural hegemony of biomedicine will not be achieved overnight. Changing people's health behavior is a significant challenge. To maintain health sustainability, we must reach the entire community, including rural and remote areas, and work together with local indigenous stakeholders to bridge the gaps in sociocultural understanding. Resources that enhance the quality of life can have a significant influence on population health outcomes. By applying what we know about the Social Determinants of Health (SDH), we may not only improve population health but also advance health equity. The author offers a participant observation, discussing the social determinants based on self-experience living in an indigenous community in Asmat. This article aims to provide an overview of SDH in Asmat through the approach of medical anthropology, as the SDH may potentially have roles in health outbreaks, especially in the case of malnutrition and measles in early 2018.